Control factors on the composition of superficial sediments in estuaries of the coast of Huelva : un acercamiento estadístico - Borrego, J; Carro, B; Grande, J.A; de la Torre, M.L; Valente, T; Santisteban, M (Journal of Iberian geology, 2013)
The geochemical composition of surface sediments has been analyzed for the following three river estuaries located in the Huelva coast (SW Spain): Guadiana, Piedras and Tinto-Odiel (Ria de Huelva), which represent an area strongly affected by mining activity, mainly for Cu exploitation in the Iberian Pyrite Belt. The main goal of the present study was to evaluate the water and sediment quality of the three estuary systems, which have been subject to different types of anthropogenic activity. Enrichment factors (EF) for several elements were determined for each system, using as reference the composition of the sediments from the Huelva Ria, prior to the intensive mining and industrial activity. Statistical treatment based on factorial analysis allowed establishing the origin of the elements and the main control factors of their geochemical behaviour in the estuarine systems. The estuary of Tinto- Odiel rivers (Ria de Huelva) presents high metal concentrations and strong EF for metals related to acid mine drainage, namely Cu (EF of 75,6), Zn (EF of 36,9), and Pb (EF of 58), indicating severe environmental quality problems. On the contrary, the sediments of the Guadiana and Piedras rivers show no significant EF. Here, the obtained results indicate the absence of antropic metallic contributions, which permits the maintenance of the environmental quality of both systems. Thus, the present study revealed the environmental quality problems of the sediments from Tinto-Odiel estuary, while in Guadiana and Piedras there are no significant metallic contributions, ensuring the maintenance of the their environmental quality. Keywords: Metal pollution, Sediments, Iberian Peninsula, Estuary, Tinto-Odiel, Piedras, Guadiana. Se ha analizado la composicion geoquimica de los sedimentos superficiales en tres estuarios localizados en la costa de Huelva (SO de Espana), un area fuertemente afectada por la actividad industrial y por la extraccion minera de cobre en la Faja Piritica. Estos estuarios corresponden a los rios Guadiana, Piedras y Tinto y Odiel (Ria de Huelva). La finalidad de este estudio es comprobar la calidad de las aguas y de los sedimentos en tres sistemas estuarinos que han estado sometidos a diferente actividad antropica, destacando factores de enriquecimiento (EF) para varios elementos en los tres sistemas, usando como referencia la composicion de los sedimentos de la Ria de Huelva, antes de la intensa actividad minera e industrial. Se llevo a cabo un tratamiento estadistico basado en analisis factorial con el fin de establecer el origen de los elementos y los factores de control principales de su comportamiento geoquimico en los sistemas estuarinos. El estuario del Tinto-Odiel (Ria de Huelva) presenta altas concentraciones metalicas y factores de enriquecimiento (EF) fuertes para metales relacionados con el drenaje acido, a saber Cu (EF de 75,6), Zn (EF de 36,9) y Pb (EF de 58), lo que indica problemas severos sobre la calidad ambiental. Al contrario, los sedimentos del Guadiana y rio Piedras no muestran ningun EF significativo. Respecto a estos dos sistemas, los resultados obtenidos indican la ausencia de contribuciones metalicas antropicas, lo que permite al mantenimiento de la calidad ambiental de ambos sistemas. Este estudio permite asegurar que los sedimentos del estuario Tinto-Odiel presentan una mala calidad ambiental, mientras que el caso de los estuarios del Guadiana y Piedras no se observan contribuciones antropicas significativas de metales y se pueden considerar que mantienen una buena calidad ambiental. Palabras clave: Contaminacion por metales, sedimentos, Peninsula Iberica, estuario, Tinto-Odiel, Piedras, Guadiana